A cross-sectional exploration of the clinical characteristics of disengaged (NEET) young people in primary mental healthcare. Issue 12 (23rd December 2014) - O'Dea, Bridianne; Glozier, Nicholas; Purcell, Rosemary; McGorry, Patrick D; Scott, Jan; Feilds, Kristy-Lee; Hermens, Daniel F; Buchanan, John; Scott, Elizabeth M; Yung, Alison R; Killacky, Eoin; Guastella, Adam J; et al.
Abstract : Objective: Youth with mental health problems often have difficulties engaging in education and employment. In Australia, youth mental health services have been widely established with a key aim of improving role functioning; however, there is little knowledge of those who are not engaged in employment, education or training (NEET) and the factors which may influence this. This study aimed to examine NEET status and its correlates in a sample of such youth. Design: Cross-sectional data from a longitudinal cohort study. Setting: Between January 2011 and August 2012, young people presenting to one of the four primary mental health centres in Sydney or Melbourne were invited to participate. Participants: Young adults (N=696) aged between 15 and 25 years (M=19.0, SD=2.8), 68% female, 58% (n=404) attended headspace in Sydney. Measures: Individuals 'Not in any type of Education, Employment or Training' in the past month were categorised as NEET. Demographic, psychological and clinical factors alongside disability and functioning were assessed using clinical interview and self-report. Results: A total of 19% (n=130/696) were NEET. NEETs were more likely to be male, older, have a history of criminal charges, risky cannabis use, higher level of depression, poorer social functioning, greater disability and economic hardship, and a more advanced stage of mental illness than those engaged in education, training or work. Demographics such as postsecondary education, immigrant background and indigenous background, were not significantly associated with NEET status in this sample. Conclusions: One in five young people seeking help for mental health problems were not in any form of education, employment and training. The commonly observed risk factors did not appear to influence this association, instead, behavioural factors such as criminal offending and cannabis use appeared to require targeted intervention.